Possibilities of supportive therapy in patients with blood system tumors and malignant neoplasms - V. B. Larionova; A. V. Snegovoy (Онкогематология, 2020)
Finding opportunities to improve treatment outcomes of cancer patients remains a difficult and unresolved problem. Modern anticancer treatment due to the intensity and molecular biological orientation allows achieving higher efficiency and theoretically reducing the complications frequency. At the same time, the “increase in efficiency” in the modern oncology really exists, but a “decrease in the incidence of complications” is far from its solution. In many ways, the problems of diagnosis, treatment and monitoring of complications are associated with the impact on complex physiological processes in the body of an oncological patient. Timely implementation of modern and adequate programs for the prevention and treatment of these complications defines the concept of “supportive therapy”, which provides at least half of the effectiveness of anticancer treatment.The Multinational Association of Supportive Care in Cancer (MASCC) was formed in 1990. The main tasks of the association were the creation of supportive care system, its popularization and accumulation of scientific data. The MASCC was used not only oncologists experience, but also of specialists working in almost all areas of medicine. Supportive therapy provides prevention and treatment of complications from the moment of malignant disease develops, at all stages of anticancer treatment, during the rehabilitation period, and in patients in the terminal phase.An important stage in the development of maintenance care in Russia was the holding of annual conferences in Moscow with the support of MASCC. Russia is included in the European MASCC group and in working group on supportive therapy and palliative care of the Chemotherapists Society (ESMO). The Russian Society of Supportive care in Oncology (RASSC) was organized In Russia on June 1, 2017. In recent years, the main directions of supportive care have been developed in our country. Today, supportive therapy is an obligatory component of anticancer programs, which allows the patient to cope with severe but potentially reversible disorders of vital organs at all stages of treatment. This is a real way to increase the treatment efficacy and improve the quality of life of cancer patients.